Intramural ectopic pregnancy: An individual patient data systematic review - Carnot N. Ntafam; ItunuOluwa Sanusi-Musa; Robert D. Harris (European Journal of Obstetrics & Gynecology and Reproductive Biology: X, 2024)
Intramural pregnancies (IMP) are very rare and represent about 1% of ectopic pregnancies (EPs). Despite a few reported cases, there is limited awareness & knowledge among sonographers and physicians. Moreover, no established diagnostic or treatment protocol exists for such a condition. This study identifies and synthesizes what is known about IMP, including etiology and pathophysiology, common clinical presentations, imaging features, laparoscopic and hysteroscopic findings, and management. PUBMED and Google Scholar were queried to identify eligible studies. All articles on IMP in human subjects available in English and French languages were included. Other types of ectopic pregnancies, including cesarean scar and cervical ectopic pregnancies, were excluded. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines and a narrative synthesis approach were used to systematically review the medical literature. 82 cases distributed around 27 countries with an average maternal age of 32.07 years and gestational age of 9.27 weeks were eventually selected for this study. History of curettage was the most common risk factor reported in 30 (36.58%) patients, followed by history of salpingectomy, assisted reproduction with embryo transfer, and previous cesarean delivery, in 10(12.19%), 10(12.19%), and 9(10.97%) patients respectively. Ultrasound was performed in 80(97.56%) cases. Of the 66 reported ultrasound findings, 29 were diagnostic or suggestive of IMP. MRI, laparoscopy (both diagnostic & surgical) and diagnostic hysteroscopy were carried out on 18(21.95%), 36(43.9%) and 22(26.83%) patients respectively. Histopathologic examination mainly performed after surgery was the gold standard for confirming the diagnosis. Management involved conservative (3.65%) approach, medical treatment with methotrexate or potassium chloride (23.17%), and surgical interventions. The latter includes laparoscopic surgery (25.61%), laparotomic surgery (23.17%), and hysterectomy (13.41%). IMP is a rare but potentially lethal clinical entity. A significant proportion of patients are asymptomatic and have no known risk factors. Correlation between clinical history and imaging findings is vital to establish a prompt diagnosis and reduce the risk of a catastrophic outcome.